O espaço livre público na habitação social em Araguari, Minas Gerais Uma avaliação do papel da legislação urbanística no quadro projetual do sistema de espaços livres públicos em cinco conjuntos habitacionais produzidos entre 1965 e 2015 - Corrêa, Michelle dos Santos (2016)
This research aims to understand how the urban legislation affects the production processes of the Public Open Spaces System in Social Housing Sets, produced in the city of Araguari - Minas Gerais between the years of 1965 to 2015, in order to increase knowledge about the complex process of formation of the peripheric urban landscapes. It was evaluated how the projective parameters set by town planning legislation, had impacted in the design and in the appropriation conditions of social housing sets and your public open spaces system, from the urbanistic design proposal to the current reality of deployments. It started from the hypothesis that lack of obligation of a landscape design for the urban project approval by city hall contributes significantly to the lack of urban environmental quality that the public open spaces system of these sets has, directly impacting on the qualification of peripheric urban landscapes. It was observed from the analysis of the sets, from the perspective of its public open spaces such as town planning legislation has allowed consolidating a housing model increasingly reductionist, hostile and segregating.